Sustainable Development of Mineral-Raw Complex - SHUGAIPOVA, Zhanna; ERNUR, Mukhtar; KUANYSH, Ayazhanov; ABDRAKHMANOVA, Akmaral (Journal of Environmental Management and Tourism, 2018)
At present, the acute question of rational resource consumption and resource saving arises in the republic. Sustainable development of the economy of Kazakhstan should be based on the planned and effective use of natural resources, in terms of the combined use of raw materials by enterprises of the mineral and raw materials complex. The current situation at the enterprises of the mineral and raw materials complex testifies to the need for the further development of the enterprise management system in order to obtain an additional chain of surplus value by passing out valuable components from raw materials. In connection, fundamental scientific research is needed, which makes it possible to scientifically substantiate improvement of the enterprise management system, the results of which can significantly improve the efficiency of the enterprise in the rational use of raw materials, both in terms of its processing, and in the direction of preserving the ecology of the region.